A Unique Protein Self-Assembling Nanoparticle with Significant Advantages in Vaccine Development and Production. (4th January 2020) - Carter, Daniel C.; Wright, Brenda; Jerome, W. Gray; Rose, John P.; Wilson, Ellen
Abstract : Nanoparticles are playing an increasingly powerful role in vaccine development. Here, we report the repurposing of nonstructural proteins 10 and 11 (hereafter NSP10) from the replicase polyprotein 1a (pp1a) of the human SARS coronavirus (severe acute respiratory syndrome) as a novel self-assembling platform for bioengineered nanoparticles for a variety of applications including vaccines. NSP10 represents a 152 amino acid, 17 kD zinc finger transcription/regulatory protein which self-assembles to form a spherical 84 Å diameter nanoparticle with dodecahedral trigonal 32 point symmetry. As a self-assembling nanoparticle, NSP10 possesses numerous advantages in vaccine development and antigen display, including the unusual particle surface disposition of both the N- and C-termini. Each set of N- or C-termini is spatially disposed in a tetrahedral arrangement and positioned at optimal distances from the 3-fold axes (8-10 Å) to nucleate and stabilize the correct folding of complex helical or fibrous trimeric receptors, such as those responsible for viral tropism and cell infection. An application example in the exploratory development of a therapeutic vaccine for idiopathic pulmonary fibrosis (IPF), including preliminary analysis and immunogenic properties, is presented. The use of this system could accelerate the discovery and development of vaccines for a number of human, livestock, and veterinary applications.